HUBUNGAN EKSPEKTASI USAHA DAN EKSPEKTASI KINERJA DENGAN PEMANFAATAN REKAM MEDIK ELEKTRONIK DI INSTALASI RAWAT JALAN RUMAH SAKIT UMUM CUT MEUTIA KABUPATEN ACEH UTARA TAHUN 2022 - Afrilius Simanjuntak; Akhmad Fatikhus Sholikh; Elmina Tampubolon; Marlen Sadrina Br Sitepu (Jurnal Penelitian Kesmasy, 2022)
The implementation of RME will be able to provide effective and efficient management of patients, doctors and clinics as well as improve good outcomes for hospitals. The purpose of the study was to determine the relationship between business expectations and performance expectations with the use of electronic medical records by outpatient installation officers at the Cut Meutia General Hospital, North Aceh Regency in 2022. The type of research is quantitative research, the nature of the research is cross-sectional. This research was conducted at the outpatient installation of the Cut Meutia General Hospital, North Aceh. The study population was all employees in the outpatient installation, totaling 337 people. The sample in the study amounted to 185 people. The results showed that there was a relationship between business expectations and the use of electronic medical records in the outpatient installation of the Cut Meutia General Hospital, North Aceh. There is a relationship between performance expectations and the use of electronic medical records in the outpatient installation of the Cut Meutia General Hospital, North Aceh. It is recommended to the management of the Cut Meutia General Hospital, North Aceh in an effort to further increase business expectations and productivity of officers' performance in order to encourage and motivate officers to continue their education to a higher level or attend seminars in accordance with their disciplines.